Incidence of self-reported tuberculosis treatment with community-wide universal testing and treatment for HIV and tuberculosis screening in Zambia and South Africa: A planned analysis of the HPTN 071 (PopART) cluster-randomised trial. - L Telisinghe; S Floyd; D MacLeod; A Schaap; R Dunbar; J Bwalya; N Bell-Mandla; E Piwowar-Manning; D Donnell; K Shaunaube; P Bock; S Fidler; et al. (PLoS Medicine)
Background HIV is a potent risk factor for tuberculosis (TB). Therefore, community-wide universal testing and treatment for HIV (UTT) could contribute to TB control, but evidence for this is limited. Community-wide TB screening can decrease population-level TB prevalence. Combining UTT with TB screening could therefore significantly impact TB control in sub-Saharan Africa, but to our knowledge there is no evidence for this combined approach. Methods and findings HPTN 071 (PopART) was a community-randomised trial conducted between November 2013 to July 2018; 21 Zambian and South African communities (with a total population of approximately 1 million individuals) were randomised to arms A (community-wide UTT and TB screening), B (community-wide universal HIV testing with treatment following national guidelines and TB screening), or C (standard-of-care). In a cohort of randomly selected adults (18 to 44 years) enrolled between 2013 and 2015 from all 21 communities (total size 38,474; 27,139 [71%] female; 8,004 [21%] HIV positive) and followed-up annually for 36 months to measure the population-level impact of the interventions, data on self-reported TB treatment in the previous 12 months (self-reported TB) were collected by trained research assistants and recorded using a structured questionnaire at each study visit. In this prespecified analysis of the trial, self-reported TB incidence rates were measured by calendar year between 2014 and 2017/2018. A p-value ≤0.05 on hypothesis testing was defined as reaching statistical significance. Between January 2014 and July 2018, 38,287 individuals were followed-up: 494 self-reported TB during 104,877 person-years. Overall incidence rates were similar across all arms in 2014 and 2015 (0.33 to 0.46/100 person-years). In 2016 incidence rates were lower in arm A compared to C overall (adjusted rate ratio [aRR] 0.48 [95% confidence interval (95% CI) 0.28 to 0.81; p = 0.01]), with statistical significance reached. In 2017/2018, while incidence rates were lower in arm A compared to C, statistical significance was not reached (aRR 0.58 [95% CI 0.27 to 1.22; p = 0.13]). Among people living with HIV (PLHIV) incidence rates were lower in arm A compared to C in 2016 (RR 0.56 [95% CI 0.29 to 1.08; p = 0.08]) and 2017/2018 (RR 0.50 [95% CI 0.26 to 0.95; p = 0.04]); statistical significance was only reached in 2017/2018. Incidence rates in arms B and C were similar, overall and among PLHIV. Among HIV-negative individuals, there were too few events for cross-arm comparisons. Study limitations include the use of self-report which may have been subject to under-reporting, limited covariate adjustment due to the small number of events, and high losses to follow-up over time. Conclusions In this study, community-wide UTT and TB screening resulted in substantially lower TB incidence among PLHIV at population-level, compared to standard-of-care, with statistical significance reached in the final study year. There was also some evidence this translated to a decrease in self-reported TB incidence overall in the population. Reduction in arm A but not B suggests UTT drove the observed effect. Our data support the role of UTT in TB control, in addition to HIV control, in high TB/HIV burden settings. Trial registration ClinicalTrials.gov: NCT01900977.